Intellectual Capital Disclosure and Its Effect on The Cost of Equity Capital in The Manufacturing Industry Indonesia - Rini Rini; Lies Zulfiati; Muhammad Anhar (BPJP - STEI, 2021)
This study aims to test the influence between Intellectual capital disclosure and its components (Human capital, structural capital, and relational capital) on manufacturing companies listed on the Indonesia Stock Exchange from 2015 to 2019. This research is quantitative with a causality approach. The intellectual capital disclosure measurement method uses an index developed, and the cost of equity capital is measured by the Capm method. The study's results did not negatively impact intellectual capital disclosure, and the two components are human capital disclosure and relational capital disclosure with the cost of equity capital. However, the results confirmed the hypothesis of negative and significant influence between structural capital disclosure and the cost of equity capital.